Analisis dalam Penentuan Strategi Usaha Kafe Coffee Legend Kota Bandar Lampung - Riswan; Suprihadi; Nata, Andrian Anwar L (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2024)
This research aims to determine a suitable strategy for the Coffee Legend Cafe business in Bnadar City, Lampung. The research uses qualitative research with observation and documentation techniques. The data analysis tool in this research is SWOT analysis (SWOT (Strengths Weaknesses, Opportunities and Threats). SWOT analysis is an analysis technique for measuring the strengths, weaknesses, opportunities and threats of a company. By creating an analysis table, it is then measured through the SWOT quadrants in the Cartesian diagram. The results of this SWOT analysis research were analyzed using the Internal Strategic Factor Analysis Summary or IFAS and the External Strategic Factor Analysis Summary or EFAS. The results of the IFAS and EFAS calculations found points (0.12 and -0.64), on the Cartesian diagram. It is in a Conservation strategy with Strengths and Threats (ST).